El estudio para el control informático de los partes diarios de los trabajos realizados por los técnicos de corporación nacional CNT. - Romero Cano, Diana Wendy (2017)
This paper describes the development of a case study that is framed in the lines and sub lines of investigation of the career of engineering in systems, and that mainly involves the development of software and the benefits when dealing with topics related to technologies ; also to the improvement of the efficient control with its use when making daily parts in the corporation CNT. Computer systems are very necessary tools for organizations that need efficiency, secure storage of information is already a necessity and a common denominator in all business, private and public companies have tools to deal with large amounts of information saved a great deal amount of time and money. (Garreta, 2003) The National Telecommunications Corporation of the city of Babahoyo is not far removed from this technological introduction, where the main interpreter of computer systems makes up the information and documentation that is generated as such, which are performed in physical form in parts of work that are delivered daily by technicians of said institution. The process studied is that at the end of a working day, the daily work is done based on the information generated from activities that must be reported during the working day of each technician of the CNT.